1998
DOI: 10.1103/physrevb.57.8518
|View full text |Cite
|
Sign up to set email alerts
|

Specific heat of liquid3Heunder pressure in a restricted geometry

Abstract: We have investigated the specific heat of liquid 3 He confined to an Ag sinter with an average pore size of about 1000 Å in the temperature range 1 mKрTр20 mK and at pressures 4.8 barр pр34.0 bar. The specific heat of normal-fluid 3 He in the sinter pores shows the linear temperature dependence expected for a Fermi liquid. However, the effective mass of the 3 He quasiparticles is clearly enhanced in the restricted geometry compared to data obtained in bulk 3 He. In addition, there is a temperature-independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…2 In contrast to the past results Schrenk and König reported the new result that the constant heat capacity in the silver sinter is several times as large as the constant heat capacity in the Vycor glass. 4 They presented new issues of whether the constant heat capacity depends on the substrate, i.e., silver or Vycor, and whether it depends on liquid or solid. We intend to resolve these issues by measuring the heat capacity for both the liquid and solid 3 He on the same substrate.…”
Section: Introductionmentioning
confidence: 99%
“…2 In contrast to the past results Schrenk and König reported the new result that the constant heat capacity in the silver sinter is several times as large as the constant heat capacity in the Vycor glass. 4 They presented new issues of whether the constant heat capacity depends on the substrate, i.e., silver or Vycor, and whether it depends on liquid or solid. We intend to resolve these issues by measuring the heat capacity for both the liquid and solid 3 He on the same substrate.…”
Section: Introductionmentioning
confidence: 99%
“…For measurements of the heat capacity this latter approach is preferable. Earlier experiments [20,21,22] of this kind show that the heat capacity differs from that of the bulk, without a consensus for interpretation. Greywall suggested that there is a healing length of the superfluid at the surface [20].…”
mentioning
confidence: 98%
“…Greywall suggested that there is a healing length of the superfluid at the surface [20]. Others have argued [21,22] that there is a broad distribution of transition temperatures of disconnected superfluid regions. In our experiment we use a high resolution temperature sweep method that can provide sufficient detail to explore the temperature and 3 He obtained from a slow warm up trace at 11.31 bar.…”
mentioning
confidence: 99%